2018
DOI: 10.18203/2320-1770.ijrcog20184149
|View full text |Cite
|
Sign up to set email alerts
|

Profile of infection in women with vaginal discharge in North India

Abstract: Background: The objective of the present study was to observe the profile of infection in women with vaginal discharge.Methods: The present study was conducted between October 2013 and September2014. The respondents were females in reproductive age group (15-45 years) attending Obstetrics and Gynaecology OPD with history of vaginal discharge. After detailed clinical examination of the patient, pH was determined, and the posterior fornix was swabbed with a cotton tip applicator. Further a Whiff (amine) test don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
3
2
0
Order By: Relevance
“…The most common type of discharge seen in patients of BV was gray-white in the present study which is comparable to study by Sood and Sud [19] and Masand et al [17]. We found that lower abdominal pain was significantly associated with patients of BV and VVC contrast to study documented from Maharashtra [20] and Yemen [18], where pruritus was the significantly associated symptom with VVC.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The most common type of discharge seen in patients of BV was gray-white in the present study which is comparable to study by Sood and Sud [19] and Masand et al [17]. We found that lower abdominal pain was significantly associated with patients of BV and VVC contrast to study documented from Maharashtra [20] and Yemen [18], where pruritus was the significantly associated symptom with VVC.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study (2%) is comparable to studies conducted in Puducherry (5.5%) [16] and Maharashtra (6.36%) [20], whereas Himachal Pradesh describes much higher mixed infection rate (34.5%) [19]. The etiology of mixed infection is comparable to study from Maharashtra but contrasts with the maximum etiology of BV+TV from Puducherry.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These infections if not treated or ignored could debilitate the patients and could become a source of infection for the neonate especially in case of women belonging to the childbearing age. 6 Etiologies associated with vaginitis are multiple and establishing the etiology helps in successful management and prevention of complications. 7 In our study the vaginal infections with one or the other organism detected in 31% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli (Doderlein's bacilli), Group B and D streptococci, Coagulase negative Staphylococci, Diptheroids etc., inhibit the growth of harmful flora. 2 The extremes of age are more prone for vaginal infections.…”
Section: Introductionmentioning
confidence: 99%